The role of MscL amphipathic N terminus indicates a blueprint for bilayer-mediated gating of mechanosensitive channels - Navid Bavi; D. Marien Cortes; Charles D. Cox; Paul R. Rohde; Weihong Liu; Joachim W. Deitmer; Omid Bavi; Pavel Strop; Adam P. Hill; Douglas Rees; Ben Corry; Eduardo Perozo; et al. (Nature Communications, 2016)
The activation of bacterial mechanosensitive channels is still not fully understood. Here, Bavi et al. show that the N-terminal helix of MscL dynamically couples membrane tension to channel gating, suggesting a conserved mechanism underlying the mechanosensitivity of ion channels of higher organisms.